Usaha Produktif Disabilitas Sensorik dan Fisik Komunitas Teras Inklusi Melalui Budidaya Ikan Nila Sistem RAS Biostimulan Bak Bundar: Productive Efforts for Sensory and Physical Disabilities through Nile Tilapia Cultivation Using a Circular Biostimulant RAS System in the Teras Inklusi Community - Kisworo, Yulius; Mukhlisah, Mukhlisah; Erziaty, Rozzana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The community empowerment program based on Nile tilapia cultivation using the biostimulant RAS system was expected to enhance their economic independence. The main challenges included limited access to information, education, and technology, as well as a lack of support in business management. The program aimed to address these issues and provide a positive impact on the welfare of the disability community. The activity titled 'Productive Efforts for Sensory (Hearing Impairment/Deafness) and Physical Disabilities through Nile Tilapia Cultivation Using a Circular Biostimulant RAS System in the Teras Inklusi Community' was conducted using a Participatory Rural Appraisal (PRA) approach. The installation of the circular RAS (Recirculating Aquaculture System) ponds in the field proceeded as planned, with all system components, such as the circular ponds, filtration system, and water distribution pipes, installed correctly and functioning properly. During the installation process, coordination between the PKM team and partners was effective, resulting in no significant obstacles. The training activity successfully enhanced the participants' understanding and competencies significantly. Evaluation results showed an increase in the number of participants categorized as Good from 25% in the pre-test to 85% in the post-test. Furthermore, no participants were in the Poor category after the training.